Academic Challenges in Developmental Coordination Disorder: A Systematic Review and Meta-Analysis. (2nd January 2023) - Dionne, Eliane; Bolduc, Marie-Ève; Majnemer, Annette; Beauchamp, Miriam H.; Brossard-Racine, Marie
Abstract: Aims: Developmental Coordination Disorder (DCD) is a chronic condition affecting motor coordination in daily activities. While motor difficulties are well documented in this population, it is unclear how frequent and to what extent academic activities are affected. This systematic review aims to comprehensively summarize the knowledge regarding the prevalence and extent of academic difficulties in reading, writing and mathematics in school-aged children with DCD. Methods: Two independent reviewers analyzed original studies on academic difficulties in school-aged children with DCD. A binary random-effects model was used to calculate the pooled prevalence by academic difficulty. A random-effects model using standardized mean differences (g statistic) was calculated to estimate the extent of the academic difficulties. Results: Twenty-four studies were included. A pooled prevalence of 84% of handwriting difficulties and 89.5% of mathematical difficulties was reported. No pooled prevalence of difficulties could be calculated for the other academic outcomes. Children with DCD present with poorer performance in handwriting legibility (g = −1.312) and speed (g = −0.931), writing (g = −0.859), mathematics (g = −1.199) and reading (g = −1.193). Conclusions: This review highlights the high frequency and severity of academic difficulties in children with DCD, specifically in mathematics, which stresses the importance of evaluating academic performance to target interventions to support optimal functioning in daily life.